Ritual reform and ritual behavior - Amundsen, Arne Bugge (Traditiones (Ljubljana), 2012)
The article focuses on the complex question of continuity and change as exemplified by ritual policies and ritual practices during the Lutheran reformation in 16th century Denmark-Norway. Thematically the article concentrates on matrimony and funeral. A main point is that despite changes in liturgy and church organisation motivations and practices demonstrate a remarkable continuity. The most eclatant change seems to have taken place in the field of ritual entrepreneurship: The Lutheran clergy lost control thus leaving initiative and interpretation to the congregations.
Keywords: ethnology; Etnologija; customs; Šege; religion; Rituali; Poroka; wedding; Pogreb; funeral; Danska; Denmark; Norveška; 16.st.; Religija; Protestantism; Protestantizem; ljudske šege; poroke; pogrebi